2016
DOI: 10.1080/24701394.2016.1261854
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic study on few morphotypes of a patellogastropod Cellana karachiensis from northern Arabian Sea reveals unexpected genetic diversity

Abstract: A group of limpets, Cellana karachiensis, exhibiting phenotypic plasticity were examined from Gujarat coastline India, using molecular phylogeny. Previous examination of the COI genes established the presence of three different haplotypes X, Y and Z, while present study showed three more haplotypes X, X and Z. Thus, a total of six COI gene haplotypes, having 99.23% to 99.85% sequence similarity, were observed with variations at six sites. Bayesian phylogenetic analysis shows divergence of lineages X-Y, X-X and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…shell banding patterns) can indicate breaks in the lineage and beginning of speciation for other limpets (e.g. Joseph et al ., 2018). However, such phenomena have not been investigated for L. subrugosa populations on the Brazilian coast and, based on the available literature, L. subrugosa is the only abundant limpet occurring in our study sites (Rios, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…shell banding patterns) can indicate breaks in the lineage and beginning of speciation for other limpets (e.g. Joseph et al ., 2018). However, such phenomena have not been investigated for L. subrugosa populations on the Brazilian coast and, based on the available literature, L. subrugosa is the only abundant limpet occurring in our study sites (Rios, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting work byJoseph et al (2014) revealed the presence of three cryptic species of limpet Cellana karachiensis from Veraval with different shell color banding pattern and indicated a close molecular resemblance to Oman species populations using the COI gene. The research was extended further byJoseph et al (2016b) in terms of coverage of study area (five sites along Gujarat coast) and genetic markers (COI and 16S). The study demonstrated the existence of six haplotypes of C. karachiensis with phenotypic plasticity in the study region, suggesting initiation of the speciation.…”
mentioning
confidence: 99%